1980
DOI: 10.1002/1097-0142(19801115)46:10<2238::aid-cncr2820461021>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Infantile digital fibromatosis. Ultrastructural, histochemical, and tissue culture observations

Abstract: Three cases of infantile digital fibromatosis were studied by electron microscopy, enzyme histochemistry, and tissue culture. The tumors were made up equally of myofibroblasts containing electron-dense inclusions which were composed chiefly of microfilaments measuring about 5 to 7 nm. Dense bodies usually observable in the smooth muscle cells were found in the bundles of these microfilaments and in the process of the inclusions, suggesting that these inclusions may represent an abnormal accumulation of contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 8 publications
2
22
0
Order By: Relevance
“…Morphologically, the growth is composed of proliferating spindle-shaped cells, with ultrastructural features of myofibroblasts (Bhawan et al 1979, Iwasaki et al 1980, Mortimer & Gibson 1982, Iwasaki et al 1983, Zina et al 1986). The most peculiar feature of the neoplastic cells is the presence of intracytoplasmic inclusion bodies, which are now regarded, on the basis of the meromyosin binding assay (Iwasaki et al 1983) and of immunocytochemical investigations (Fringes et al 1986, Zina et al 1986), as strictly related to contractile proteins, being most probably composed of actin filaments or degradation products of actomyosin.…”
Section: Introductionmentioning
confidence: 99%
“…Morphologically, the growth is composed of proliferating spindle-shaped cells, with ultrastructural features of myofibroblasts (Bhawan et al 1979, Iwasaki et al 1980, Mortimer & Gibson 1982, Iwasaki et al 1983, Zina et al 1986). The most peculiar feature of the neoplastic cells is the presence of intracytoplasmic inclusion bodies, which are now regarded, on the basis of the meromyosin binding assay (Iwasaki et al 1983) and of immunocytochemical investigations (Fringes et al 1986, Zina et al 1986), as strictly related to contractile proteins, being most probably composed of actin filaments or degradation products of actomyosin.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusions frequently contain small, lucent membrane-bound vesicles, which resemble cell organelles or could represent entrapped cell organelles. 1,20,22 Fingerlike processes can be seen extending from the inclusions; these processes show the same structure as the bundles of microfilaments and sometimes contain dense bodies. Other features seen in the spindled cells are multiple indentations of the nucleus, abundant cisternae of rough endoplasmic reticulum, a prominent Golgi complex, many pinocytotic vesicles, and no viral particles.…”
Section: Ancillary Studiesmentioning
confidence: 98%
“…The bundles run parallel to the long axis of the cells, appear like microtendons, and have been shown to attach to the cell membrane. 1,20,22 The characteristic feature present in most cells is the electron-dense, non-membranebound, spherical inclusions within the cytoplasm. The inclusions measure 1 to 10 nm in diameter and appear to vary in maturity, with the smaller inclusions having an irregular, poorly defined border, and the larger inclusions appearing round and sharply demarcated.…”
Section: Ancillary Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…25,66 A highly characteristic morphologic finding in the spindled cells of IDF and first reported by Reye n 1965 66 is the presence of a rounded, eosinophilic, 1.5 40 to 24 mm, 68 paranuclear cytoplasmic inclusion with distinct histochemical properties. 66,68 Ultrastructural and immunohistochemical analyses of the lesion have demonstrated that the key cellular element is a myofibroblast 12,19,32,35,39,52,53 and that the cytoplasmic inclusion consists primarily of aggregated actin microfilaments. 19,28,32,35,40 Although many of the salient clinical and pathologic features of IDF have been documented in the literature, several clinical and pathobiologic aspects of the process remain unresolved.…”
mentioning
confidence: 99%